Community Perceptions of Talawi District against Regional Head Elections as a Means to build Local Democracy - Ananda Mahardika; Faizal Hamzah Lubis (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Regional head elections (Pilkada) are one of the means used to demonstrate the democratic value of a government. Practically the activities and actions that apply in the pilkada are adopted from the general election system prevailing in Indonesia. Therefore, the pilkada is expected to be able to form local democracy in the regions. However, the facts show that the implementation of the pilkada actually shows the apathy of the people in the elections. According to the author's observations, the apathy of the people in the elections is inseparable from the perceptions formed by the community towards the pilkada. This perception then shapes people's behavior that distorts the objectives of the pilkada as a means of building local democracy in the region. Therefore this study aims to see how people's perceptions of the pilkada as a means of building local democracy. Especially in the Talawi sub-district, Batu Bara Regency. In this study the authors used quantitative research methods to measure people's perceptions of the elections as a means of building local democracy in the regions. From the results of the research conducted, it can be seen that the people of Talawi sub-district give negative perceptions of the pilkada. The community doubts the ability of the pilkada as a means of building local democracy in the region.